The Analysis of the Benefit of Jamu (Indonesian Traditional Medicine) and Herbal Medicine and Its Effect on Women of Childbearing Age - Harismayanti Harismayanti; Sabirin B. Syukur (Journal of Community Health Provision, 2022)
The aim of this research is to find out the benefit of herbal medicine for health service in primitive communities, especially women of childbearing age. The research team applied mixed-method and used questionnaire and exploratory survey by doing interview and direct observation to collect the data. The result of the research showed that there were 68 samples of women(100%) after childbirth or in childbearing age consumed herbal medicine. There were eight types of medicinal herbs that people consumed, they were turi leaf (Sesbania Grandiflora), binahong leaf (Anredera Cordifolia (tenore) steen), gedi leaf (Abelmoschus Manihot L), katuk leaf (Sauropus Androgynus), turmeric, ginger, jamu gendong (jamu being carried on the back) and herbal medicines (jamu) in sachets. The existence of cultural aspects that continue for generations caused the high use of herbal medicines. People gradually felt great benefits of consuming herbal medicines with less or even none negative impacts. It was easy to find herbal medicines or jamu in the market. That is the big reason why people, especially women of childbearing age, prefered consuming herbal medicines than other medicines. The government and related institutions should be able to control the use of this herbal medicines. Legal license of medicines has to be controlled to avoid bad impacts on people, especially women of childbearing age.